Pengenaan Sanksi Terhadap Pramuwisata yang Tidak Berijin dalam Bidang Perjalanan Wisata - Timothy Reinaldi Winata; Ketut Kasta Arya Wijaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
Tourism affairs are one of the elective matters that are closely related to the superior potential and regional peculiarities This research is important to do with the aim of knowing the setting of sanctions against unlicensed tour guides in the field of travel agencies regulated in the Bali Provincial Regulation Number 5 of 2016 This research will be carried out using normative legal research, normative legal research is used because it examines and analyzes laws tourism Setting Sanctions Against Unlicensed Tour Guides in the Field of Travel Bureaus Regulated in the Bali Provincial Regulation in accordance with Regional Regulation Number 5 of 2016 Article 15 paragraphs (1) and (2) states that : Every General Tour Guide as referred to in Article 2 letter a, is required to have an KTPP to carry out tourist guiding duties Everyone who violates the provisions as referred to in Article 3 paragraph (1) shall be punished with imprisonment for a maximum of 3 (three) months or a fine of a maximum of Rp.50,000,000 as for Administrative Sanctions in the form of verbal warnings and freezing of KTPP.